Solitary fibrous tumor of the orbit - Inoue, Eri; Tanoe, Natsuko; Bohara, Manoj; Mori, Nasanao; Hosoyama, Hiroshi; Nishimuta, Yosuke; Sueyoshi, Kazunobu; Nakayama, Hirofumi; Sakimoto, Yoshihiro; Tokimura, Hiroshi (Nepal Journal of Neuroscience, 2001)
Intracranial solitary fibrous tumor (SFT) / Hemangiopericytoma (HPC) is a rare mesenchymal tumor. The occurrence in the orbit is quite rare, with only 2/244 cases in the Japanese population of primary tumors in the orbit. Herein, we report the case of a 54-year-old woman who presented with right visual disturbance. The vision had worsened and was lost after a year. Three years later, magnetic resonance image (MRI) revealed a right intraorbital tumor, and 16 years later, swelling of the right eyelid and exophthalmos appeared. Computed Tomography scan revealed a well-defined homogeneous mass in the orbito-cranial communicating region, and MRI revealed a 30 mm mass lesion compressing the right optic nerve, presenting with low signal intensity on T1-weighted image (T1WI) and T2-weighted image with heterogeneous contrast effects. Also, dynamic contrast-enhanced T1WI revealed slow signal enhance effect. The lesion was surgically resected via right frontotemporal craniotomy. Histopathological examination of the lesion revealed SFC. Immunopathologically, the tumor was negative for S-100, glial fibrillary acidic protein, epithelial membrane antigen, synaptophysin, while was positive for cluster of differentiation 34, B cell/chronic lymphocytic leukemia lymphoma 2. Moreover, signal transducer and activator of transcription 6 was positive in intranuclear, and Ki-67 was negative in most of the cells. The postoperative course is uneventful without recurrence after 4 years. SFT of the orbit should be considered as a differential diagnosis although it is extremely rare disease. It is similar to meningioma and schwannoma and we should take Dynamic-Contrast-Enhanced MRI for preoperative diagnosis. Careful postoperative follow-up is needed because some cases report recurrence and malignant transformation.